PENGARUH TARIF PAJAK, TUNNELING INCENTIVE, MEKANISME BONUS DAN EXCHANGE RATE TERHADAPTRANSFER PRICING (STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTURYANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2013-2016) - Shelly Viviany; Ria Nelly Sari; Riska Natariasari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
This study aims to examine the influence of tax rate, tunneling incentive, bonus plan and exchange rate on trsnsfer pricing. Transfer pricing is a dependent variable in this study that measured with sales to related parties. Independent variable in this study are tax rate, tunneling incentive, bonus plan and echange rate. The sample of this research are the manufacture firms listed in Indonesian Stock Exchange in 2013-2016. The sample are collected using purposive sampling method and resulted 136 firms become the samples. Data analyzed by coefficient of determination test and examination hypothesis by logistic regression analysis. The result of this research show that tax rates and bonus plan do not have a significant effect to transfer pricing. While the other variable, tunneling incetive and exchange rate have significant effect to transfer pricing.Keywords : Transfer pricing, Tax Rate, Tunneling Incentive, Bonus Plan and Exchange Rate